Functional nano-composite oxides synthesized by environmental-friendly auto-combustion within a micro-bioreactor - Zhou, W.; Shao, Zongping; Ran, R.; Jin, W.; Xu, N. (Pergamon, 2008)
Nano-crystalline Sm0.2Ce0.8O1.9 (SDC), Gd0.2Ce0.8O1.9 (GDC), La0.6Sr0.4Co0.2Fe0.8O3-d (LSCF) and NiO (65 wt.%)-GDC powders for applications in solid-oxide fuel cells were synthesized by employing cotton fibers as the micro-bioreactor. As compared with the conventional glycine-nitrate (GN) combustion method, this novel process allows the preparation process to be more environmental-friendly. Furthermore, the particle size of obtained powders could be smaller, attributing to the blocking effect of cellulose on suppressing the particle contact during synthesis. By this innovative method, SDC powder with a particle size as small as ~10 nm, was obtained, which can be easily sintered to dense electrolytes at 1350 °C. The process is also capable for large-scale synthesis. © 2007 Elsevier Ltd. All rights reserved.